"The Traps Started During My Childhood": The Role of Substance Abuse in Women's Responses to Adverse Childhood Experiences (ACEs). Issue 4 (21st April 2021) - Boppre, Breanna; Boyer, Cassandra
ABSTRACT: The gendered pathways perspective seeks to identify the biological, psychological, and social realities that lead to women's law-breaking behavior. Prior research in this area demonstrates the link between women's adverse childhood experiences (ACEs) and involvement in the criminal justice system later in life. The current study fills an important gap in the literature by providing a phenomenological description of the impacts ACEs had upon 19 community supervised women's lives. Their stories illuminate the need to consider multiple forms of ACEs, from physical and sexual abuse to the death of a loved one. Interviewees' most prevalent response to ACEs was substance abuse. Three major themes related to their pathways to substance abuse emerged: coping/self-medication, escaping insecure households, and familial influences. Narratives were developed around each theme to provide an in-depth understanding of women's ACEs and substance abuse. Theoretical and policy implications for women involved in the criminal justice system are discussed.